Electrically controlled enhancement in plasmonic mid-infrared photodiode - Tobing, Landobasa Yosef Mario (2019)
Surface plasmon polaritons (SPPs) have been attracting tremendous attention in application of enhanced optoelectronic devices owing to their capability of localizing electromagnetic waves in deep subwavelength scale. We propose a plasmonic mid-infrared InAsSb-based n-i-p photodiode with electrically-controlled photocurrent enhancement achieved by controlling the overlap between SPP depth and the absorption layer, from which maximum electrically controlled enhancement factors of ~5x and ~6x have been achieved for room temperature (293 K) and 77 K operation, respectively, corresponding to electrical tuning factors of 11.9 and 26. The maximum detectivities obtained at the two temperatures are 0.8 × 1010 Jones and 5 × 1011 Jones, respectively. This electrically controlled enhancement expands the application capability of plasmonic photodiodes.